2018
DOI: 10.1002/jlb.1hi1017-396rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: IL-18 primes murine NK cells for proliferation by promoting protein synthesis, survival, and autophagy

Abstract: Combined stimulation by IL-2 and IL-18 effectively promotes proliferation of NK cells, whereas singular stimulation does not. In this study, synergistic effects of these cytokines on NK cells proliferation was analyzed, focusing on the roles of IL-18. In splenic resting NK cells from IL-18KO mice, IL-18 rapidly activated NF-κB independently of IL-2, and activated or up-regulated various molecules downstream of PI3K/AKT and mTOR, including S6, Bcl-XL, ATG5, and LC3II, accompanying increases in cell growth and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 49 publications
(95 reference statements)
2
25
1
Order By: Relevance
“…IL‐18 has been previously documented as a synergistic cytokine, enhancing function of NK cell stimulatory cytokines such as IL‐2, IL‐12, IL‐15, IL‐18, and IL‐21 through activation and metabolism pathways . Indeed, our results confirmed that combining IL‐15 and IL‐18 induced extremely rapid NK cell proliferation, far exceeding the rate of IL‐15 alone.…”
Section: Discussionsupporting
confidence: 80%
“…IL‐18 has been previously documented as a synergistic cytokine, enhancing function of NK cell stimulatory cytokines such as IL‐2, IL‐12, IL‐15, IL‐18, and IL‐21 through activation and metabolism pathways . Indeed, our results confirmed that combining IL‐15 and IL‐18 induced extremely rapid NK cell proliferation, far exceeding the rate of IL‐15 alone.…”
Section: Discussionsupporting
confidence: 80%
“…Importantly, both cytokines were induced as a result of ch14.18/CHO and not IL- cytotoxic NK cells and cytotoxic T lymphocytes that may largely contribute to the clinical benefit. 39,[48][49][50] Since co-treatment with IL-2 led to a strong induction of immune suppressive T regs , the concomitant depletion of T regs during an IL-2 treatment or replacing IL-2 by cytokines which do not stimulate immune suppressive cell populations may represent potential strategies for future. [51][52][53] In summary, our study provides a mechanistic explanation for the absence of a beneficial role of IL-2 for immunotherapy with ch14.18/CHO as previously reported 13 due to its undesired expansion of immune regulatory T regs .…”
Section: Discussionmentioning
confidence: 99%
“…In this capacity, IL‐18 is recognized as a Th1 response inducing factor alongside IL‐12, and indeed requires the presence of IL‐12 to elicit this function. As well as enhancing IFNγ expression from CD 4+ T cells, IL‐18 can also work in concert with IL‐12 to drive NK cell effector function and expression of IFNγ, and induce NK cell expansion through enhanced IL‐2 sensitivity . IL‐18 induces such responses through stimulating a unique heterodimeric receptor consisting of IL‐18Rα ligand binding and IL‐18Rβ accessory chains.…”
Section: Interleukin‐18mentioning
confidence: 99%